2007
DOI: 10.1038/sj.ejcn.1602728
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of assessment methods for self-reported alcohol consumption in health interview surveys

Abstract: Objective: To select a simple method for assessing alcohol consumption and to compare how different reference periods and response categories influence the self-reported frequency of binge drinking. Design: Four random samples of 1000 adult Danes. Data were collected via personal interview at the respondents' home. Setting: Denmark, nationwide. Participants: The total number of interviewed was 2593 individuals. Measurements: The assessment methods in the four samples were (1) the 7-day recall method, (2) intak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 29 publications
(36 reference statements)
1
31
0
Order By: Relevance
“…The TLFB is a widely accepted methodology to collect detailed and reliable self-reported exposure (29, 34). This method was tailored to our studied populations and modified to collect more precise, serial information throughout pregnancy, allowing evaluation of drinking patterns across time (27).…”
Section: Discussionmentioning
confidence: 99%
“…The TLFB is a widely accepted methodology to collect detailed and reliable self-reported exposure (29, 34). This method was tailored to our studied populations and modified to collect more precise, serial information throughout pregnancy, allowing evaluation of drinking patterns across time (27).…”
Section: Discussionmentioning
confidence: 99%
“…Studies in other populations indicate that the use of AUDIT questions can reflect current drinking habits [3133] and can be used to detect temporal trends in consumption [34]. Data comparing self-reported consumption for different temporal scales show good correlations [8, 35], and the patterns in our data suggest as much since we observed a reported modest increase in binge drinking events during the festive season followed by a decrease in January and February (as well as during the summer period). These are however, likely biased downwards as a result of the longer reference period [9, 36].…”
Section: Discussionmentioning
confidence: 99%
“…First, the information related to demographic, socioeconomic, and life style-related factors was self-reported in health surveys, and thus might be subject to information bias and/or recall bias. Although the alcohol consumption measured in household surveys might be underreported [34], it is possible to use such questions in epidemiological studies [35]. In addition, studies have shown that self-reported information regarding risk factors, including alcohol consumption and smoking, was reasonably reproducible, suggesting reasonable reliability [36], [37].…”
Section: Discussionmentioning
confidence: 99%